Effect of teleradiology on patient waiting time and service satisfaction in public hospitals, Northwest Ethiopia: a quasi-experimental study - Araya Mesfin Nigatu; Tesfahun Melese Yilma; Lemma Derseh Gezie; Yonathan Gebrewold; Monika Knudsen Gullslett; Shegaw Anagaw Mengiste; Binyam Tilahun (BMC Health Services Research)
Abstract Background Limited access to onsite radiologists in Low- and Middle-Income Countries (LMICs) poses challenges for health facilities in delivering timely radiology services resulting in prolonged patient waiting times and dissatisfaction with the insufficient radiology services. In recent years, teleradiology has emerged as a potential solution to improve the timely diagnosis and treatment process. Therefore, this paper analysed the effect of a web-based teleradiology system that was developed and deployed to evaluate its effect on patient waiting time and service satisfaction in public hospitals of the Amhara Regional State. Methods A pre-post study design was employed to evaluate the effect of a web-based teleradiology system on patient waiting time and service satisfaction. The study included a total of 836 participants, out of which 417 participated during the pre-intervention and 419 in the post-intervention periods. Data were collected from October 2021 to February 2022 and from May 2022 to January 2023 for the pre-and post-implementation periods, respectively. Supportive measures, including user guides, onsite training, and onsite/virtual assistance, were given during the teleradiology implementation period. The effects of the teleradiology on waiting time and service satisfaction were evaluated with the Mann-Whitney U-test and the Generalized Linear Model. Waiting time was measured as the duration between image consultation and report completion. Furthermore, satisfaction was assessed using a 31-item, 5-point Likert scale. The statistical analysis was done using Stata version 17 software. Results After the implementation of the web-based teleradiology system, a significant decrease in the median waiting time was observed from 43.5 h (IQR: 22.88–71.63) to 4.62 h (IQR: 2.52–10.53) (p-value < 0.01). The effect size for this improvement was found to be 0.84. Furthermore, the median patient satisfaction score was significantly improved from 96 (IQR: 89–103) to 113 (IQR: 105–124) (p-value < 0.01) and an effect size of 0.65. Similarly, the percentage of the scale mean score (%SM) showed an increase in patient satisfaction levels from 52.6% (pre-implementation) [95% CI: 51.8–53.5] to 65.7% (post-implementation) [95% CI: 64.5 -66.9%]. The GLM analysis demonstrated a 71% decrease in patient waiting time and an 11% increase in radiography service satisfaction (p-value < 0.01). Conclusion Implementing the web-based teleradiology system improved the patient’s waiting time and service satisfaction remarkably. The notable reduction in waiting time and the significant improvement in patient satisfaction scores highlighted the benefits of teleradiology in enhancing timely diagnosis and treatment. Deploying a web-based teleradiology system in public hospitals is recommended to enhance efficiency and improve patient satisfaction in radiology consultations. Trial registration number PACTR202401789144564. Trial registration date 09 January 2024.